THE WOOD BEYOND THE WORLD: JÄMTLAND AND THE NORWEGIAN KINGS - Alex Woolf (Brill, 2007)
This paper looks at Jämtland, a province now in Sweden but, until the seventeenth century considered a dependency of the Norwegian crown. The paper considers the textual and archaeological evidence that Scandinavian (as opposed to Saami) settlement in the region originated from Trondelag, in Central Norway, and goes on to look at the conflicting accounts of how the region came to be considered under the unified Norwegian crown. It is further argued that, whilst contiguous with the Kingdom, Jämtland, as a semi detached autonomous community, had much in common with Norway's Atlantic colonies west oversea.